2015
DOI: 10.1039/c5nr00494b
|View full text |Cite
|
Sign up to set email alerts
|

Carrier transport in quantum dot quantum well microstructures of the self-assembled CdTe/CdS/ligand core–shell system

Abstract: The study on the quantum dot quantum well (QDQW) microstructure modified by choosing different ligands containing a sulfhydryl group is of significance because it enables one to regulate photoexcited free charge carriers' (FCCs') transport behaviours in high-quality CdTe/ligand QDs via a self-assembled way. The photoelectron characteristics of ligand-capped CdTe nanoparticles were probed by a combination of surface photovoltaic (SPV) and photoacoustic technologies, supplemented by a computer simulation method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…The particle density ρr c 3 is 3. The three DPD particles are contained in a cube of r c 3 and therefore correspond to a volume of 270 Å 3 due to the volume of a water molecule being 30 Å 3 . Thus, the physical value of the unit of length r c is (270) 1/3 Å = 6.463 Å, which was previously derived by Groot and Rabone to fit the measured diffusion constant of water.…”
Section: ■ Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The particle density ρr c 3 is 3. The three DPD particles are contained in a cube of r c 3 and therefore correspond to a volume of 270 Å 3 due to the volume of a water molecule being 30 Å 3 . Thus, the physical value of the unit of length r c is (270) 1/3 Å = 6.463 Å, which was previously derived by Groot and Rabone to fit the measured diffusion constant of water.…”
Section: ■ Methodsmentioning
confidence: 99%
“…For example, the optical transparency of liquid crystal displays is controlled by the regular arrangement of particles, and the viscosity of coating materials is controlled by self-assembled surfactants. Moreover, self-assembled materials have been developed, such as micelles, , quantum dots, , and nanomachines. , Thus, it is crucial to predict and control the self-assembly of nanoparticles. Designing colloidal particles with anisotropic shapes and chemical interactions is an effective method to control the morphologies of self-assembled nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22][23][24][25][26][27] In our previous works, the self-assembled core-shell CdTe/CdS/ligand, CdSe/CdS/ligand, and ZnSe/ZnS/ligand QDs were prepared via the aqueous synthesis way, respectively. [28][29][30][31] The results revealed that the ligand and the shell layer played not negligible roles in the gradual energy band structure of these QDs. For examples, the ligand not only improved the stability of the QDs, but also may change the transport mechanism and adjust the transmission channel of photogenerated free charge carriers (FCCs) in these QDs.…”
Section: Introductionmentioning
confidence: 93%
“…However, they both have advantages and disadvantages with respect to their photoelectric characteristics. Nanocrystal particles exhibit strong photon absorption productivity for generating carriers in the extended bands, resulting in efficient carrier collection. , However, a photoelectric device with a channel layer composed of nanoparticles can exhibit unfavorable carrier transport of the generated carriers; the surface/interface trap-modulated hopping and tunneling processes dominate the performance of such devices. , The photodetectors based on thin films of semiconductor nanocrystal particles demonstrate remarkably high responsivities accompanied by slow responses; meanwhile, large driving voltages are commonly requested . To achieve high gain and low dark current, a large electrode spacing (>5 mm) is needed to allow more photons to be absorbed; the transit time of the charges across the electrodes is correspondingly increased, and the applications of these photodetectors are thus limited. By contrast, semiconductor nanowires possess ideal transport characteristics with optimal carrier mobility, exhibiting nonnegligible dark current. , Therefore, during the past decade, nanowire-based ultraviolet (UV) photodetectors have been widely explored, with most efforts focusing on single nanowires or arrays because their merits of high crystal quality and facile fabrication make them suitable for fabricating optoelectronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 However, a photoelectric device with a channel layer composed of nanoparticles can exhibit unfavorable carrier transport of the generated carriers; the surface/ interface trap-modulated hopping and tunneling processes dominate the performance of such devices. 12,13 The photodetectors based on thin films of semiconductor nanocrystal particles demonstrate remarkably high responsivities accompanied by slow responses; meanwhile, large driving voltages are commonly requested. 14 To achieve high gain and low dark current, a large electrode spacing (>5 mm) is needed to allow more photons to be absorbed; the transit time of the charges across the electrodes is correspondingly increased, and the applications of these photodetectors are thus limited.…”
Section: Introductionmentioning
confidence: 99%